1977
DOI: 10.1111/j.1600-051x.1977.tb01887.x
|View full text |Cite
|
Sign up to set email alerts
|

Root surface roughness in response to periodontal instrumentation studied by combined use of microroughness measurements and scanning electron microscopy

Abstract: Root surface roughness, resulting from calculus removal by hand curette, ultrasonic curette and rotating diamond or Roto-Pro points, was examined by combined use of microroughness measurements and scanning electron microscopy (SEM). Mandibular incisors were placed in a jaw model with a rubber "gingiva" in an attempt to simulate a clinical situation. After cleaning with the various instruments, the surface roughness was measured by an industrial profilometer followed by SEM evaluation. A microroughness index (M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
40
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 82 publications
(45 citation statements)
references
References 25 publications
2
40
1
Order By: Relevance
“…Only one study reported about higher Ra values after using a hand curette in comparison to an ultrasonic system or Er:YAG laser [16]. As already described by others [14,15], a smear layer after using Gracey curettes was always visible in the SEM photographs. In the present study, the smear layer was clearly reduced following the additional by use of the diamond-coated curette.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Only one study reported about higher Ra values after using a hand curette in comparison to an ultrasonic system or Er:YAG laser [16]. As already described by others [14,15], a smear layer after using Gracey curettes was always visible in the SEM photographs. In the present study, the smear layer was clearly reduced following the additional by use of the diamond-coated curette.…”
Section: Discussionmentioning
confidence: 76%
“…Moreover, it appears that the observations made 30 years ago which have indicated that ultrasonic and rotating diamond instruments produced more uneven surfaces than hand curettes [14] are still valid today. It has been shown that after ultrasonic instrumentation, the surfaces appeared irregular and had grooves [15], and they were rougher compared to the surfaces obtained following the use of a curette [7].…”
Section: Discussionmentioning
confidence: 97%
“…To do so, scaling is performed using hand [7,8], ultrasonic [7,9,10] or sonic instruments [11,12]. Whilst hand instrumentation is both challenging and time-consuming but allows direct tactile control [13], power-driven instruments are easier to use and sometimes require less time than hand instruments to successfully debride root surfaces [14]. It is speculated that especially less experienced operators might not be sufficiently successful in removing subgingival plaque or calculus when using hand instruments, whilst inducing damages on the root surfaces with these instruments [15].…”
Section: Introductionmentioning
confidence: 99%
“…Whilst being technically challenging and time demanding, an effective root surface instrumentation during supportive periodontal therapy (SPT) with hand instruments allows excellent direct tactile control and assessment of the treatment and its results [1,2]. In contrast, power-driven instruments, which are rather blunt and use acceleration of the vibrating tip to disrupt the plaque [3], seem easier to use which might explain why practitioners increasingly prefer power-driven over hand instruments [4,5].…”
Section: Introductionmentioning
confidence: 97%